HUBUNGAN STRESS DENGAN KENAIKAN KADAR GULA DARAH PADA PENDERITA DIABETES MELITUS DI RUANG DHOHORSUD Prof Dr SOEKANDAR MOJOSARI - Wahyuni, Lutfi (JURNAL KEPERAWATAN SEHAT, 2015)
The purpose of this study was to determine the correlation of stress with the increase of blood glucoselevel in diabetes mellitus patient in Ruang Mawar RSUD Sidoarjo. The study used Correlational Analytic design with Cross Sectional approach. The population was all the patients with diabetes mellitus in Ruang Dhoho RSUD Prof Dr Soekandar Mojosari (44 patient) and 24 patients were taken as sample by purposive sampling. The independent variable was thestress levels and the dependent variable was the blood glucose level. The data was taken using questionnaires and Digital Glukotest. Data was processed and continuedwith Spearmans Rho statisticaltest using SPSS 16. The results showed ρ (0.012) <α (0.05), so that H0was rejected. This means that there is correlation of stress with the increase of blood glucoselevel, with cc = 0.502 shows a strong correlation. Patients with diabetes mellitus is expected to communicate with their family or medical personnel in overcome the stress that arises in order to speed up healing.Key words: Stress, Increase in BloodGlucoseLevels